Pendidikan Agama Islam: Solusi Mengatasi Perilaku Menyimpang Siswa SMK Negeri 1 Kendari - La Hadisi (Institut Agama Islam Negeri Kendari, 2013)
Abstract:This research uses description qualitative methods, the collected data usingobservation, interviews,and doccumentation. Data the data obtained areaccumulated, described, and analyzed by the Researcher's own arguments.Informants in this reseach is the principal, vice the principal of the students,teachers of islamic religious, guidence and conselling, chairman of thestudents, vice chairman of the vocational students SMK N 1 Kendari. Basedon the research that there is 15 types of ekstrakokurikuler activities whichdevelop in SMK N 1 Kendari has been running with excellent suppressdeviant behavior. Example, it always doing IMTAQ [read yasin ], kultumfriday, zakat charities raise infaq and charity, welcomed the guidance oframadhan islamic religious tourist, has worked with teachers regardingstudents who are troubled, al qur'an literacy, late coaching, training timesgraffi, wall islamic magazine and organizes the race each end of semester.Kata Kunci: Peran Pendidikan Agama Islam dan Prilaku Menyimpang